2022
DOI: 10.1530/eor-21-0067
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation rates after proximal femur fracture fixation with single and dual screw femoral nails: a systematic review and meta-analysis

Abstract: Purpose The purpose of this study was to investigate differences in aseptic reoperation rates between single or dual lag screw femoral nails,in the treatment of intertrochanteric fractures (ITF) in elderly patients. Methods Electronic databases were searched for RCTs and prospective cohort studies treating elderly ITF patients with a single or dual screw femoral nails. Data for aseptic reoperation rates between single screw, dual separated screw and dual integrated screw devices were pooled using a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
2
0
2
Order By: Relevance
“…[ 23 ] Furthermore, two recent meta-analyses have concluded that additional studies are necessary to assess the effectiveness of intramedullary nails and to determine which design is more suitable for the fixation of intertrochanteric femur fractures. [ 24 , 25 ] It is important to note that maintaining fracture reduction during surgery is quite difficult and technically demanding. [ 26 ] Our clinical experience with reverse oblique fracture intramedullary nailing indicates that these fractures, particularly those with posterolateral fragments, present challenges.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Furthermore, two recent meta-analyses have concluded that additional studies are necessary to assess the effectiveness of intramedullary nails and to determine which design is more suitable for the fixation of intertrochanteric femur fractures. [ 24 , 25 ] It is important to note that maintaining fracture reduction during surgery is quite difficult and technically demanding. [ 26 ] Our clinical experience with reverse oblique fracture intramedullary nailing indicates that these fractures, particularly those with posterolateral fragments, present challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the nail brands providing a helical blade (short and long PFNA) had risk of reoperation comparable to the other brands. Double lag screws have been introduced to some nail designs to potentially reduce the risk of rotational instability, fracture collapse, and failure, but there is no definitive clinical evidence suggesting superior results 35,36 . In our study, the long TRIGEN TAN/FAN and the long T2 Recon nail provide double lag screws.…”
Section: Discussionmentioning
confidence: 99%
“…Sobre a reabordagem, essa foi necessária em apenas uma minoria dos pacientes e após dois anos da cirurgia. Segundo Sivakumar et al (2022), os mecanismos de falha que contribuem para a necessidade de reabordagem cirúrgica variaram entre os tipos de dispositivos, com dispositivos de parafuso duplo separados exibindo vários mecanismos de falha que não costumam ser relatados em dispositivos de parafuso integrados simples ou duplos. Dentre esses mecanismos, destacam-se a quebra de parafuso de retardo, efeito z/reverso, protrusão medial do parafuso de compressão e necrose avascular da cabeça femoral.…”
Section: Discussionunclassified
“…Além disso, para dispositivos de duplo parafuso integrado, cutout e fratura periprotética normalmente são os únicos mecanismos relatados. Ainda, para dispositivos de parafuso único e parafuso separado duplo, cut-out, fratura periprotética e retrocesso do parafuso de compressão são os mecanismos que mais contribuem para as taxas de reabordagem (SIVAKUMAR et al, 2022).…”
Section: Discussionunclassified